THE EFFECT OF USING PINTEREST MEDIA ON STUDENTS’ ABILITY IN DESCRIPTIVE WRITING FOR GRADE X AT SMAS GKPI PADANG BULAN - Mei Br. Siringo-ringo; Fenty Debora Napitupulu; Harpen Silitonga (Program Studi Pendidikan Bahasa Inggris, 2025)
This study examines the effect of utilizing Pinterest as a teaching tool on the descriptive writing abilities of SMAS GKPI Padang Bulan students in the tenth grade. The issue raised in this study is the difficulty students face in developing ideas, enriching vocabulary, and enhancing creativity in writing. The objective of this research is to determine whether Pinterest, as a visual-based platform, can enhance students' descriptive writing skills. The research method used is a quantitative experimental method involving two classes: class X-3 as the experimental group and class X-1 as the control group, each consisting of 26 students. Both groups were given a pre-test to measure the students' initial writing abilities. The experimental group was taught using Pinterest, while the control group was taught using conventional methods. After the treatment, a post-test was conducted to measure the improvement in writing skills. The research results show that the average score of the experimental group significantly increased from 61.38 to 77.23, while the control group increased from 54.81 to 67.27. The results of the t-test showed a t-value of 2.557, higher than the t-table value of 2.010 at a significance level of 0.05. This indicates a significant difference between the two groups. Thus, the use of Pinterest has a positive and significant impact on students' descriptive writing skills and can be considered an effective and innovative learning tool in teaching writing at the high school level.